Utilization of e-Book Kotobee Reader as an Interactive Learning Tool in Developing 8th Grade Mathematical Skill - M Otico; M Pasion; JAY-R DONES (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
When the COVID-19 pandemic broke out in our country, the education sector explored the availability of technologies that might be helpful to ensure the delivery of quality education to learners despite the sudden shift in learning modality, that is, from face-to-face to blended learning. The Sulong Edukalidad, a move of the Department of Education to innovate Philippine Education under COVID-19 provided online training and webinars that prepared Filipino teachers in facing the new normal of the education setting. One of which is the utilization of the e-book Kotobee Readers as an interactive learning tool. E-books are one of the many software programs being developed to enhance teaching in the field of education. E-books are publications that can give students information and instructions in the form of multimedia flexibly and efficiently, thereby supporting and improving learning. In this regard, our team aims to explore the potential of the utilization of the e-book Kotobee reader as an interactive learning tool for developing 8th Grade Mathematical skills during the Covid-19 pandemic, focusing on the average percentage of the participants before and after the utilization of the e-book, their level of performance during the utilization of the said learning material, the challenges encountered by the participants and also identifying the positive traits of Kotobee that helped the students learn. The research design to be used for this research will be a quasi-experimental approach. This research design is intended for an interventional study used to estimate the impact of an interactive–based lesson using the Kotobee e-book on the Grade 8 students in developing their mathematical skills The participants involved in this research are the selected Grade 8 – Rose learners in Mataas na Paaralang Neptali A. Gonzales Our team implemented a series of interventions about topics in Quarter III which the lectures and activities can be found in the said e- book. Students’ usage of the Kotobee e-book app daily was tracked in an Inquiry report. Students’ scores in each activity will be tallied at the end of each quarter for assessment. This will assist us in determining how well the students performed after they have used the Kotobee e-book. A separate learning activity sheet (LAS), validated by the Master Teacher in charge of JHS Mathematics, was administered weekly to be able to validate the performance of the learners for a specific topic taught while using the e-Book. At the end of the Quarter, a post-test was administered to be able to determine the performance of the students. Data collected showed that using the Kotobee e-book, it has affected how well the participants do in Mathematics 8 Quarter III, as shown by the significant difference between the mean percentage scores on the pre-test and the mean percentage scores on the summative test. Students learn while using the Kotobee e-book, based on the results of their weekly assessments and their quarterly test.